Some Biological Aspects of Freshwater Lobsters, Cherax quadricarinatus, in Ralik River of Southeast Minahasa and in Tondano Lake of Minahasa - Rinaldi Kuhu; Rose O.S.E Mantiri; John L. Tombokan (Sam Ratulangi University, 2019)
The purpose of this study was to determine the relationship between the length of weight, the growth patterns and the biological conditions of freshwater crayfish, Cherax quadricarinatus, in two different locations namely river and lake. Sampling in Ralik river of Southeast Minahasa, used a sibu-sibu fishing gear (salapa) by traversing the river (opposite the current) from the point of the pick up location until the sampling point taken. As for sampling at Tondano Lake of Minahasa, it was carried out by buying directly from local fishermen who used bubu as a fishing tool. Furthermore, samples from these two locations were analyzed at the Freshwater Bioecology Laboratory of FPIK UNSRAT Manado.The results obtained from this study are the linear equation of the relationship of the length of weight in the river for male lobsters W = -1.761049+ 3.1153 log L, and W = -1.647836 + 2.957268 log L for female lobsters; in the lake W = -1,494 + 2,8495 log L for males and females W = -1,388 + 2,7198 log L. The growth pattern of male and female lobsters in river and males in the lake is isometric; whereas females in allometric lakes. The value of the biological condition of the river male losbters ranged from 0.90 to 1.14 with an average value of 1.004 ± 0.06, whereas in lake male lobster the value of the condition factor ranged from 0.83 to 1.23 with an average value of 1.004 ± 0.09. The value of the condition of river female lobsters with a range between 0.82-1.18 with an average value of 1.004 ± 0.89 and the condition factor of lake female lobsters ranged from 0.90 to 1.11 with an average value of 1.001 ± 0.06. This shows that the body condition of a fat lobsters were good enough. Keywords: Freshwater Lobster, Long-weight, Growth pattern, Factor of biological conditions. ABSTAKTujuan dari penelitian ini adalah untuk mengetahui hubungan panjang berat, pola pertumbuhan faktor kondisi biologis dari lobster air tawar Cherax quadricarinatus di dua lokasi berbeda yaitu sungai dan danau. Pengambilan sampel di Sungai Ralik, Minahasa Tenggara menggunakan alat tangkap sibu-sibu (salapa) dengan cara menyusuri sungai (berlawanan arus) dari titik lokasi pengambilan sampai batas pengambilan sampel dilakukan. Adapun pengambilan sampel di Danau Tondano Minahasa, dilakukan dengan cara membeli langsung dari nelayan lokal yang memakai bubu sebagai alat tangkap. Sampel-sampel yang diperoleh selanjutnya dianalisis di Laboratorium Bioekologi Perairan Tawar FPIK UNSRAT Manado.Hasil yang didapat dari penelitian ini yakni persamaan linier hubungan panjang berat di sungai untuk jantan W = -1,761049+ 3.1153 log L, dan W = -1,647836 + 2,957268 log L untuk betina; di danau W = -1,494 + 2,8495 log L untuk jantan dan betina W = -1,388 + 2,7198 log L. Pola pertumbuhan lobster jantan dan betina di sungai dan jantan di danau adalah isometrik; sedangkan betina di danau allometrik. Nilai faktor kondisi biologis lobster jantan sungai berkisar antara 0,90-1,14 dengan nilai rata- rata 1,004±0,06, sedangkan lobster jantan danau berkisar antara 0,83-1,23 dengan nilai rata-rata 1,004±0,09. Nilai faktor kondisi lobster betina sungai berkisar antara 0.82-1.18 dengan nilai rata-rata 1,004±0,89 dan lobster betina danau berkisar antara 0,90-1,11 dengan nilai rata-rata 1,001±0,06. Hal ini menunjukkan bahwa kondisi badan lobster cukup baik. Kata kunci : Lobster air tawar, Panjang-berat, Pola pertumbuhan, Faktor kondisi biologis.